2005
DOI: 10.1080/j.1440-1614.2005.01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Diseases of White Matter and Schizophrenia-Like Psychosis

Abstract: Production of psychotic symptoms may result from functional asynchrony of interdependent regions, due to alterations in critical circuits as a result of pathology. The nature, location and timing of white matter pathology seem to be the key factors in the development of psychosis, especially during the critical adolescent period of association area myelination. Diseases that disrupt the normal formation of myelin appear to cause psychosis at higher rates than those that disrupt mature myelinated structures. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 140 publications
(209 reference statements)
3
34
0
Order By: Relevance
“…5 This novel finding advanced our current knowledge revealed by multiple lines of evidence implicating abnormal Oligs and myelin in schizophrenia. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Also, it is consistent with the clinical observation that QUE has direct effects on negative symptoms and cognitive deficits of patients with schizophrenia. 46,47 Indeed, the alterations in white matter have been considered to be associated with the negative symptoms of schizophrenia.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…5 This novel finding advanced our current knowledge revealed by multiple lines of evidence implicating abnormal Oligs and myelin in schizophrenia. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Also, it is consistent with the clinical observation that QUE has direct effects on negative symptoms and cognitive deficits of patients with schizophrenia. 46,47 Indeed, the alterations in white matter have been considered to be associated with the negative symptoms of schizophrenia.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, a number of white matter disorders are associated with schizophrenia-like psychosis at a rate greater than chance. 15 Given that oligodendrocytes (Oligs) are myelinforming cells in the brain, it is unlikely that Oligs are spared in schizophrenia. In fact, as early as 1938, swollen Oligs were observed in schizophrenia brains postmortem.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that myelination is essential for social experience-based cognition and motor skill learning [31][32][33] [34][35][36] , abnormalities of the myelin sheath may contribute to defects of neuronal function. Increasing evidence has shown that the impairment of white matter integrity is prominent in schizophrenic brains [10,11,14,15] and further underscores the importance of the myelin sheath in schizophrenia, pointing to myelin repair as a potential therapeutic strategy for schizophrenia. In support of this notion, quetiapine, an atypical anti-schizophrenic drug, has been found to be potent in promoting the differentiation of OLs in vitro and enhancing remyelination in mouse models of demyelination [17][18][19][20] .…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, properly myelinated nerve fibers allow precise and accurate information to fl ow within and between neuronal circuits [3,8,9] . A number of imaging studies have shown that the white matter volume of schizophrenic brains is lower than in healthy controls, suggesting that myelin sheath damage or demyelination is involved in the schizophrenic brain [10][11][12][13][14][15] . In line with this hypothesis, microarray analyses have shown that genes down-regulated in schizophrenic brains are related to OL development and myelination, arguing that myelin repair may be an unmet need that has been overlooked in therapies for schizophrenia [16] .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of human brain myelination has been generally underappreciated, but recently a conceptual "myelin model" has served to correct this gap in our knowledge and provide novel and testable approaches to treatment and prevention efforts (Bartzokis, 2002;Bartzokis, 2004b;Bartzokis, 2005;Walterfang et al, 2005;Woo and Crowell, 2005). The advent of in vivo neuroimaging methods that can assess myelination on a regional basis may have direct applications in medication development (Bartzokis, 2004a;Bartzokis et al, 2004).…”
Section: Discussionmentioning
confidence: 99%